PENGARUH PENYULUHAN METODE DEMONSTRASI DAN AUDIOVISUAL TERHADAP KETERAMPILAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA WANITA USIA SUBUR DI WILAYAH KERJA PUSKESMAS PARANGINAN - Lasma Rina Efrina Sinurat; Rosetty Rita Sipayung; Yunida Turisna Oktavia Simajuntak (Jurnal Surya Muda, 2022)
Breast cancer is a type of cancer in the breast tissue that is common in women. An effort to detect the possibility of breast cancer early is to do a Breast Self-Examination (BSE), no need to spend money, just enough to take a moment. The purpose of this study was to determine the effect of demonstration and audiovisual counseling on breast self-examination (BSE) skills in women of childbearing age. This type of research is a quasi-experimental with a two group pretest-posttest design. The population in this study were all women of childbearing age and the number of samples in this study was 66 people (33 people each with demonstration and audiovisual methods) who were taken by total sampling technique. Collecting data using observation sheets or checklists. This research test uses the Wilcoxon Signed Rank Test statistical test. The results showed that the Z value = -5.477 and p-value = 0.000 (p-value <0.05), indicating that there was an effect of counseling demonstration methods on BSE skills and the Z value = -5,000 and p-value = 0.000, indicating that there was an effect of audiovisual counseling on BSE skills. It is hoped that women of childbearing age can improve their knowledge and skills in performing breast self-examination by seeking more information that is easy to understand, such as through videos and pictures to practice BSE at home and also to reduce the incidence of breast cancer in women who are expected to have their breasts checked at least once a month.